EFEKTIVITAS METODE QUALITY FUNCTION DEPLOYMENT (QFD) DALAM MENINGKATKAN KUALITAS PRODUK PADA PERUSAHAAN MAKANAN: KAJIAN LITERATUR - Rahmawati, Anisa; Machbub, Siti Salma Laila; Hakim, Rizky Firmannul (LPPM Universitas Bina Bangsa, 2024)
The quality of products (including services) produced by an industry is closely related to the satisfaction of the consumers it serves. The higher the quality of a product, the more satisfied consumers are with the usefulness, usefulness and appreciation of the product. In increasingly competitive food companies, food companies are required to produce high quality products that meet consumer expectations and desires. Product quality is a key factor that determines customer satisfaction, loyalty and long-term company success. This article aims to provide a literature review regarding the application of QFD in improving product quality in food companies as well as providing contextual knowledge as an effort to implement QFD to improve product quality. The method used in this research is a systematic literature review. The results of the literature review analyzed show that QFD is proven to have an influence on the process of improving the quality of a product or company. The research results show that QFD brings significant benefits, such as speeding up the decision-making process and increasing the match between consumer needs and product specifications. In this way, food companies can be more responsive to market changes and gain a competitive advantage by producing higher quality products. This is proven by increasing consumer satisfaction and success in maintaining or increasing market share